Penyuluhan Bank Sampah dan Pemilahan Sampah Bahan Baku Biogas Skala Rumah tangga - yani prabowo; Swasti Broto; Nazori AZ; Grace Gata; Siswanto; Yuliazmi (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2020)
In the implementation of Tridharma Peguruan Tinggi activities, especially in the field of community service, Budi Luhur University collaborates with residents of Pondok Lakah Permai Ciledug housing, to collaborate in household scale waste management to be used as biogas raw material. The problems faced by residents and environmental managers are rubbish that is not transported then decomposed, the effects of rotting garbage in the open are certainly not good for health. If the waste processing is done by burning it will cause air pollution. To overcome these problems, the waste is processed into biogas through a fermentation process. The fermentation process is used to decompose organic waste into methane gas that can be used for cooking. The role of the community is very necessary to collect raw materials for waste and sort organic and inorganic waste. The purpose of this community service activity is to provide training to residents of Pondok Lakah Permai Ciledug to separate waste from household waste to be processed into biogas and form a waste bank to collect garbage from residential residents. The method used is to provide counseling and proceed with making biodigesters to process the waste. The results achieved in this activity are that the community has understood to protect the environment and can operate biodigesters so that the garbage that had piled up is now processed into biogas.